Christ and Creation – Early Christian theologians on Christ’s ownership of creation - Van de Beek, Abram (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
Confessing a good creation was not an independent issue for early Christian theologians. They stressed creation because according to their opinion only an independent Creator can be truly God (Athenagoras). The eternal God can deal with temporal things because He is acting by his Word and Spirit (Irenaeus). The core of the doctrine of creation, however, is its Christological focus: if Christ would not be the Creator He would not have come to his own and thus would be taking someone else’s property. That would not be salvation but a crime (Irenaeus). Only after the conflicts on creation had been settled could Christian theology deal with the topic in a more relaxed sphere. That is the case in the catechetical lectures of Cyril of Jerusalem who teaches his pupils to enjoy the beauty of creation in the freedom of Christ. The early Christian approach might be an eye opener for Christians’ dealing with creation nowadays.